Przywództwo i kierowanie w ponowoczesnym świecie - Wiśniewska-Szałek, Agata (Leadership and management in the postmodern reality, 2005)
This article is presents the changes occurring in the leadership of global societies in the generation X. In the first part, the terms of postmodernism and globalization are evaluated, the latter considered to be one of key characteristics describing the generation of the next world. It also points out the changes that took place in the social aspect and economic system. In the second part of the article, the emphasis is put on the way these changes affect the manager’s leadership work as well as on the overall tendencies appearing in the leadership of the 21st century company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 222-232